Designing small molecules for therapeutic success: A contemporary perspective. Issue 2 (February 2022) - Maurer, Tristan S.; Edwards, Martin; Hepworth, David; Verhoest, Patrick; Allerton, Charlotte M.N.
Highlights: Advances in small molecule drug design have reduced molecule-based attrition. Today's design strategies must accelerate the realization of target potential. Rapid identification of risk-balanced clinical candidates enables target evaluation. Clinical experience informs meaningful differentiation strategies. Ensuring druggability of high confidence targets will improve the odds of success. Abstract: Successful small-molecule drug design requires a molecular target with inherent therapeutic potential and a molecule with the right properties to unlock its potential. Present-day drug design strategies have evolved to leave little room for improvement in drug-like properties. As a result, inadequate safety or efficacy associated with molecular targets now constitutes the primary cause of attrition in preclinical development through Phase II. This finding has led to a deeper focus on target selection. In this current reality, design tactics that enable rapid identification of risk-balanced clinical candidates, translation of clinical experience into meaningful differentiation strategies, and expansion of the druggable proteome represent significant levers by which drug designers can accelerate the discovery of the next generation of medicines.